Fracture resistance of abutment screws made of titanium, polyetheretherketone, and carbon fiber-reinforced polyetheretherketone - Eduardo Aloisio Fleck NEUMANN; Cristina Cunha VILLAR; Fabiana Mantovani Gomes FRANÇA (Sociedade Brasileira de Pesquisa Odontológica, 2014)
Fractured abutment screws may be replaced; however, sometimes, the screw cannot be removed and the entire implant must be surgically removed and replaced. The aim of this study was to compare the fracture resistance of abutment retention screws made of titanium, polyetheretherketone (PEEK) and 30% carbon fiber-reinforced PEEK, using an external hexagonal implant/UCLA-type abutment interface assembly. UCLA-type abutments were fixed to implants using titanium screws (Group 1), polyetheretherketone (PEEK) screws (Group 2), and 30% carbon fiber-reinforced PEEK screws (Group 3). The assemblies were placed on a stainless steel holding apparatus to allow for loading at 45o off-axis, in a universal testing machine. A 200 N load (static load) was applied at the central point of the abutment extremity, at a crosshead speed of 5 mm/minute, until failure. Data was analyzed by ANOVA and Tukey's range test. The titanium screws had higher fracture resistance, compared with PEEK and 30% carbon fiber-reinforced PEEK screws (p < 0.05). In contrast, no statistically significant difference was observed between the fracture resistance of the PEEK and the 30% carbon fiber-reinforced PEEK screws (p> 0.05). Finally, visual analysis of the fractions revealed that 100% of them occurred at the neck of the abutment screw, suggesting that this is the weakest point of this unit. PEEK abutment screws have lower fracture resistance, in comparison with titanium abutment screws.